The Manufacturing Process of Aluminum Hammer Molding using CNC 3 Axis for Waste Plastic in the Injection Molding Machine - H, Hendra; Reski Septiana; Dio Restu Putra Ardhika; Hernadewita; Rahmayetty; Rispandi; Hermiyetti; Gusri Akhyar (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
A process called injection molding involves cooling molten plastic after it has been injected into a mold to create a finished product. Polypropylene (PP) and polyethylene terephthalate (PETE), two basic ingredients used in plastic, are melted into a liquid and then injected into a mold. tests pertaining to the geometry of the molded product's shape and the mold's resistance at 150 °C. The mold material used in this study is aluminum 6061, and the techniques used are modeling and experimentation. The 6061-aluminum material has good temperature resistance and yields dimensional results, thickness, and shape that are almost identical to the design developed based on geometry features, which makes it suitable for use in the plastic injection process, according to the test findings.